Activin Receptor Type IIB Inhibition Improves Muscle Phenotype and Function in a Mouse Model of Spinal Muscular Atrophy - Liu, Min (PLoS One, 2016)
Spinal muscular atrophy (SMA) is a devastating neurodegenerative disorder that causes progressive muscle atrophy and weakness. Using adeno-associated virus-mediated gene transfer, we evaluated the potential to improve skeletal muscle weakness via systemic, postnatal inhibition of either myostatin or all signaling via the activin receptor type IIB (ActRIIB). After demonstrating elevated p-SMAD3 content and differential content of ActRIIB ligands, 4-week-old male C/C SMA model mice were treated intraperitoneally with 1x10(12) genome copies of pseudotype 2/8 virus encoding a soluble form of the ActRIIB extracellular domain (sActRIIB) or protease-resistant myostatin propeptide (dnMstn) driven by a liver specific promoter. At 12 weeks of age, muscle mass and function were improved in treated C/C mice by both treatments, compared to controls. The fast fiber type muscles had a greater response to treatment than did slow muscles, and the greatest therapeutic effects were found with sActRIIB treatment. Myostatin/activin inhibition, however, did not rescue C/C mice from the reduction in motor unit numbers of the tibialis anterior muscle. Collectively, this study indicates that myostatin/activin inhibition represents a potential therapeutic strategy to increase muscle mass and strength, but not neuromuscular junction defects, in less severe forms of SMA.